INDONESIA’S ACHILLES HEEL IN THE FIRST DECADE OF THE 2000s: EMPLOYMENT AND LABOUR PRODUCTIVITY IN MANUFACTURING - Maning, Chris (Masyarakat Indonesia, 2013)
In Indonesia, sluggish growth in productivity and job creation in manufacturing was particularly disappointing in the first decade of the 2000s. The work of Anne Booth has grappled with the nexus between productivity, employment and welfare in Indonesia and Asia. While she has been especially concerned with these relationships in the agricultural sector, Anne would be the first to acknowledge that some of the key relationships cut across sectors. Further, the benefits from agricultural reforms can only be broadly realized in terms of poverty reduction if better jobs are available for agricultural workers to move into in manufacturing and services as countries develop. This article takes up some of the productivity and employment relationships outside agriculture that are critical to poverty alleviation, focusing especially on labour regulations, contracts and management systems. It thus touches indirectly on a subject that has been a focus of many of Anne Booth’s writings on Indonesia since the 1980s.